Aqueous MXene/Xanthan Gum Hybrid Inks for Screen‐Printing Electromagnetic Shielding, Joule Heater, and Piezoresistive Sensor. Issue 16 (10th March 2022) - Wu, Han; Xie, Yimei; Ma, Yanan; Zhang, Binbin; Xia, Bin; Zhang, Pengxiang; Qian, Wei; He, Daping; Zhang, Xin; Li, Bao‐Wen; Nan, Ce‐Wen
Abstract: MXenes have exhibited potential for application in flexible devices owing to their remarkable electronic, optical, and mechanical properties. Printing strategies have emerged as a facile route for additive manufacturing of MXene‐based devices, which relies on the rational design of functional inks with appropriate rheological properties. Herein, aqueous MXene/xanthan gum hybrid inks with tunable viscosity, excellent printability, and long‐term stability are designed. Screen‐printed flexible MXene films using such hybrid inks exhibit a high conductivity up to 4.8 × 10 4  S m −1, which is suitable to construct multifunctional devices mainly including electromagnetic shielding, Joule heaters, and piezoresistive sensors. The average electromagnetic interference (EMI) shielding value can reach to 40.1 dB. In the Joule heater, the heating rate of printed MXene film can reach 20 °C s −1 under a driving voltage of 4 V, with a highest steady‐state temperature of 130.8 °C. An MXene‐based piezoresistive sensor prepared by the printing interdigital electrode also presents good sensing performance with a short response time of 130 ms and wide pressure region up to 30 kPa. As a result, screen‐printed MXene film exhibits reinforced multifunctional performance, which is promising for application in the next‐generation of intelligent and wearable devices. Abstract : Aqueous MXene/xanthan gum hybrid inks with tunable viscosity, excellent printability, and long‐term stability are formulated for screen printing flexible devices. The hybrid inks can be screen‐printed into diverse patterns with high conductivity and excellent mechanical flexibility, all contributing to the fabrication of multifunctional devices with outstanding EMI, Joule heater, and piezoresistive sensor performances.